Clamping force integrated computer aided tolerancing in composite assembly. (May 2021) - Wang, Hua; Yan, Chen; Yu, Junyang; Wärmefjord, Kristina
Traditional computer aided tolerancing method could not accomplish the tolerancing and variation simulation well in composite assembly. The paper presents a clamping force integrated computer aided tolerancing method for composite assembly. The stochastic variations and the stackup of variations are affected by clamping forces. The clamping force modified probability distribution is used to represent the modification based on the verified FEA model of the composite assembly. The clamping forces are coordinated based on the main deformation mode extracted by the principal component analysis to satisfy the coaxial tolerance requirements of the composite assembly. The assembly of an aircraft composite elevator is considered to illustrate the computational aspects of the proposed methods. The computer aided tolerancing method involving clamping forces outlined in the paper is found to be effective for composite assembly.